E-Therapy Autism Child with Multimedia Approach (EAMA) sebagai Intervensi Perubahan Psikomotor dan Afektif pada Anak Autis - Yena Wineini Migang; Ferdinand Mahardhika (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Autism is a brain disorder of pervasive development in children characterized by disturbances and delaysin the fields of cognitive, imagination, language, behavior, communication, and social interaction. Based on datafrom the Indonesian Autism Foundation in 2013, there are 250 thousand people in Palangka Raya City, 20% ofthem or around 50,000 are children and an estimated 100 children of autism. E-Therapy Autism Child with MultimediaApproach (EAMA) is an e-therapy created by researchers, which includes elements of e-learning. EAMAis a multimedia application software, a combination and development of autistic therapy method of Applied BehavioralAnalysis (ABA) and Treatment and education of autistic and Handicapped Children Related Communication(TEACCH). EAMA’s target target is children with autism to improve optimally cognitive, psychomotor andaffective in children with autism. EAMA facilitates interventions for behavior change, and enhances psychomotorabilities. In children with autism they are easier to receive information through audio visual. EAMA is a multimediathat can help parents at home while with autism children as an exercise, and also as a learning method forautism teachers in school while teaching. After EAMA then accompanied by practice or simulation on this partas an evaluation of the increase in the ability of autism children. This research was conducted at Sekolah KhususMelati Ceria (SKMC), Palangka Raya City, 30 people as samples, with total sampling. Experimental design withone group pre and post test, which measures the level of psychomotor and affective abilities of autism children,before and with an intervention with the application designed by the researcher, namely EAMA. Statistical analysistest with Wilcoxon. Research Results: Psychomotor level, before and after given the EAMA method ρ (0,000) <0,05and Z (-4,899), then there is the influence of EAMA method with psychomotor level before and after giving EAMAmethod. At the affective level, the value of ρ (0,000) <0,05 with a value of Z (Z -5,292, there is an effect of givingEAMA methods with an increase in affective value in children with autism.